Philippine medical thesaurus on anatomy embryonic structures and urogenital system and diseases :pathological conditions, signs and symptoms in Bikol - Lanzuela, Andrew G.; Faderon, Rosalie B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2005)
The Institute of Library and Information Science, University of the Philippines Diliman and the College of Medicine, University of the Philippines Manila teamed up for collaborative efforts in developing a Philippine Medical Thesaurus to address the need for a controlled vocabulary of medical terms. The first researches for the project were considered successful. In addition to the project the Philippine Medical Thesaurus on anatomy: Embryonic Structure and Urogenital System, and Diseases: Pathological conditions, signs and symptoms was done.
The utilization of the two approaches; i.e., building a top-down with theoretical, enumerative approach and building bottom-up with an empirical approach in thesaurus construction was done in order to meet the end of the study; to create an information tool which would cater to the information retrieval needs of the end-users. Terms were carefully sifted, relationships were well established, and organization was made for the end-uses to get a coherent and clear view of the thesaurus.
The researcher was able to translate 17 out of 61 terms for Embryonic Structures; 26 out of 77 terms for Urogenital system; and 118 out of 586 terms for Diseases; Pathological conditions, Signs and Symptoms.
The attempt to establish a bilingual thesaurus in the Bikol language proved to be difficult. The language is hard to manage with all its complexities. It is therefore recommended that the Bikol language be further studied for utilization in such projects like building a multilingual thesaurus.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Bicolano -- Medicine; Subject headings, Bicolano -- Embryology, Human -- Diseases; Subject headings, Bicolano -- Genitourinary Organs -- Diseases; Bicolano language -- Medical Bicolano